The Familyâs Entity and Challenges Along with Their Solution According to the Prophetic Tradition - Alim, Muhammad Najib (DINIKA : Academic Journal of Islamic Studies, 2016)
Family is a union resulted from an opened agreement regarding to certain mutual enjoyment, in order that both of husband and wife may comfort each other legally. It comes along with the coupleâs right and responsibilities as well. The Prophet Muhammad, even before his prophecy had taught us that family is the first social institution for any tribes or nations that elevated into this being, besides of deserving to get high position in the society. The term of family life is an ongoing issue based on the running time and place, social distinction, and different values brought such challenges that threatened modern families and hindered the aforementioned purposes. It might happen due to some factors, such as weakened familyâs role and influenced the ideal form of the family. The family will come into the rapid changes of brainstorming and facing the challenges of how to maintain the good condition, such commonly happened as result of the weakness to create religious and educational sense, which generally encountered by the modern families. Some the real problems raised today are, the women left their houses for working and the lack of children education. It is explained over this paper that Islam has already given the women right to preferring career and employment, as well as performing political role with a condition that it has made them sustainable.Keywords:family, familyâs challenge, prophetic tradition